Abbie Downes: capstone - Downes, Abbie, artist (Colorado State University. Libraries, 2015)
The artist's statement: My work deals with how I perceive the world around me, as most art does for artists. When it comes to printmaking I find I represent the natural world around me using two different methods. As a travel junkie I am always longing for my next trip and studying the world I live in. A section of this body of work includes simple, bright designs that represent specific landscapes around the world from warm desert lands to harsh cool mountains. I also explore the style of maps and create my representation of countries around the world using fine lines and bold color blocks. Both styles depict how I view the natural world and the constant beauty that existed long before us.
Colorado State University Art and Art History Department capstone project.
Capstone contains the artist's statement, a list of works, and images of works.